Hambatan Kolonisasi Methicillin Resistant Staphylococcus Aereus oleh Ekstrak Kulit Delima pada Luka Bakar Derajat-2 pada Tikus (INHIBITION OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS BACTERIA COLONIZATION ON SECOND DEGREE BURN WOUND IN WISTAR RAT BY US - Saputro, Iswinarno Doso; Zarasade, Lobredia; Prasanti, Revita Widya (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Bacterial of Methicillin Resistant Staphylococcus Aureus (MRSA) is a pathogen that plays an importantrole as a nosocomial pathogen. The bacteria can cause outbreaks of nosocomial infection which is becomeserious problems in the management of burns patients because many strains have changed intomultiresistant bacteria to several classes of antibiotics. Treatment of MRSA bacterial infection in burnsis still a problem because its cost is relatively expensive and there is an increased trend of the bacteriaresistance. Therefore, alternatives are needed to deal with these problems. One of the alternatives is byusing topical pomegranate peel extract . This study was aimed to compare the topical administration ofpomegranate peel extract with mupirocin and to evaluate the combination effect of pomegranate peelextract with mupirocin against bacterial colonization of MRSA on the burn wound rat skin. Second degreeof burn was made by placing a nail with length 2 cm and width 2 cm. Before it used, the nail was boiled inboiling water for 10 seconds. Isolates of MRSA bacteria were inoculated on burn wound in male rats strainWistar. The rats were divided into three groups, each group was treated six hours after bacterial inoculation.The first group was given mupirocin on the burn wound; the second group was given topical pomegranatepeel extract, and the third group received a combination of mupirocin with pomegranate peel extracttopically. Swab culture was taken on the third and fifth day post-treatment. The specimen was sent to theMicrobiology Laboratory for microbiological examination to evaluate the efficacy of pomegranate peel extract in inhibiting bacterial colonization of MRSA. Topical pomegranate fruit peel extract significantlyinhibited MRSA bacterial colonization on the rat’s burn wound{p sig.(2-tailed),0,045, P < 0,05). Nosignificant result was found on bacterial count in topical pomegranate fruit peel extract administationcompared to topical mupirocin administration or in combination between topical pomegranate andmupirocin. Topical pomegranate fruit peel extract has antibacterial effect, eventhough it is not moreeffective compared to mupirocin administration or combination between the pomegranate and mupirocin.
Keywords: pomegranate peel extract; antibacterial; methicillin resistant staphylococcus aureus; mupirocin